THU0413 Serum urate and its association with blood pressure and endothelial dysfunction in young adults. (15th June 2017) - Saddekni, MB; Saag, KG; Dudenbostel, T; Calhoun, DA; Oparil, S; Feig, DI; Muntner, P; Foster, PJ; Biggers, SR; Rahn, EJ; Li, P; Redden, DT; et al.
Abstract : Background: Both serum urate (sUA) and endothelial dysfunction have been associated with hypertension and cardiovascular disease. Increasing sUA level has been associated with endothelial dysfunction and higher inflammatory markers. To date, however, few studies have examined the relationship between sUA, endothelial dysfunction, and blood pressure (BP) including young and largely healthy individuals. Objectives: To determine whether there is an association between higher sUA, endothelial dysfunction as measured by flow-mediated dilation (FMD), and BP in young adults. Methods: We conducted a cross-sectional analysis of baseline data for consecutively enrolled individuals (age 18 – 40 years). Enrollment criteria included baseline systolic BP (SBP) ≥120 and <160 mmHg or diastolic BP (DBP) ≥80 and <100 mmHg, and sUA ≥5.0 mg/dL for men or ≥4.0 mg/dL for women. Endothelial dysfunction measured by FMD, 24- hours ambulatory BP monitoring (ABPM) and sUA level were obtained. Associations between sUA, FMD, and ABPM variables were evaluated using a general linear model. Adjustments for age, gender, race, and BMI were applied after significant univariate results. Results: 86 participants included in the analysis. Participants recruited had a mean age (±standard deviation) of 28.5±6.9 years, 36% were female, 41% African-Americans, mean BMI was 29.2±6.8 kg/m 2, and mean sUA was 5.9±1.2 mg/dL (n=77, range from 3.9 to 8.5 mg/dL). We found no significant cross-sectional associations between sUA, FMD, and BP variables assessed by ABPM (Table). Participants in the upper tertile of sUA had significantly worse FMD than those in the lower tertiles (Figure). However, this difference was no longer significant after multivariable adjustment age, gender, race, and BMI. Conclusions: In this cross-sectional analysis of young adults, there was no evidence to support an association between sUA levels and endothelial dysfunction or BP. Endothelial dysfunction or BP might be associated with changes in sUA when measured longitudinally in individuals, but not when measured cross-sectionally in populations. Larger studies will be needed to confirm these results. References: Ruggiero, C. Am J Cardiol, 2007. 100(1): p. 115–21. Rossi, R. J Am Coll Cardiol, 2004. 44(8): p. 1636–40. Feig, D. JAMA, 2008. 300(8): p. 924–32. Acknowledgements: National Institute of Arthritis and Musculoskeletal and Skin Diseases P50AR060772, K24AR052361 (to KGS). Disclosure of Interest: M. Saddekni: None declared, K. Saag Grant/research support from: AstraZeneca, Crealta, Takeda, Consultant for: Ardea/AstraZeneca, Crealta, Takeda, T. Dudenbostel: None declared, D. Calhoun: None declared, S. Oparil Grant/research support from: NHLBI Brigham and Women's Hospital, Center CVD Prev, Novartis Pharmaceutical Corporation, AstraZeneca AB (Duke University), Actelion Pharmaceuticals US, NIH/NHLBI, Merck and Co., Consultant for: Amgen, Bayer, Boehringer Ingelheim, AstraZeneca, Medtronic, GlaxoSmithKline, Forest Labs Inc., D. Feig: None declared, P. Muntner: None declared, P. Foster: None declared, S. Biggers: None declared, E. Rahn: None declared, P. Li: None declared, D. Redden: None declared, A. Gaffo Grant/research support from: Amgen, AstraZeneca, Consultant for: Cymabay, Ardea, Employee of: US Government